2019
DOI: 10.3390/ijms20205089
|View full text |Cite
|
Sign up to set email alerts
|

The Methylation Patterns and Transcriptional Responses to Chilling Stress at the Seedling Stage in Rice

Abstract: Chilling stress is considered the major abiotic stress affecting the growth, development, and yield of rice. To understand the transcriptomic responses and methylation regulation of rice in response to chilling stress, we analyzed a cold-tolerant variety of rice (Oryza sativa L. cv. P427). The physiological properties, transcriptome, and methylation of cold-tolerant P427 seedlings under low-temperature stress (2–3 °C) were investigated. We found that P427 exhibited enhanced tolerance to low temperature, likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Although overall genomic cytosine methylation levels of the RBSDV-infected and RBSDV-free rice plants are similar, we discovered local variations for the density profile at CG, CHG and CHH sites. Genomes of NIP infected by RBSDV undergo a global increase in DNA methylation, which is consistent with changes induced by pesticide atrazine and low-temperature [ 35 , 42 ], but is contrary to NIP exposed to Cd [ 27 ]. The CG, CHG and CHH contexts in TRV-infected Arabidopsis were slightly hypomethylated compared to mock-inoculated controls [ 16 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although overall genomic cytosine methylation levels of the RBSDV-infected and RBSDV-free rice plants are similar, we discovered local variations for the density profile at CG, CHG and CHH sites. Genomes of NIP infected by RBSDV undergo a global increase in DNA methylation, which is consistent with changes induced by pesticide atrazine and low-temperature [ 35 , 42 ], but is contrary to NIP exposed to Cd [ 27 ]. The CG, CHG and CHH contexts in TRV-infected Arabidopsis were slightly hypomethylated compared to mock-inoculated controls [ 16 ].…”
Section: Discussionmentioning
confidence: 53%
“…RBSDV is a member of the genus Fijivirus with dsRNA as genome for replication, its infection results in severe yield losses in rice [ 40 ]. Most of the work on DNA methylation of rice under stress conditions mainly focused on chilling, pesticide, drought and salinity stresses [ 35 , 41 , 42 ]. However, analysis of DNA methylation changes of rice in response to viruses, such as RBSDV, has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Omics technologies have brought about a significant breakthrough in the knowledge about plant responses to LTs [3][4][5][6][7]. In the present study, global differences in mRNAs caused by mild and moderate chilling were systematically identified and analyzed in China's most important banana cultivar with an annual yield of several million tons.…”
Section: Mild and Moderate Chilling Results In Substantial Changes Ofmentioning
confidence: 99%
“…Low temperature (LT) is one of the major environmental factors which not only limit the productivity and the geographical distribution of crops but also cause significant losses [1,2]. In recent years, modern high-throughput expression profiling techniques, such as genomics, transcriptomics, and proteomics, have provided useful tools for better understanding the roles of genes when responding to LT stresses [3][4][5][6][7]. However, most of these studies reported about the effects of severe LT (≤10 • C) on temperate [5,[7][8][9], tropical, and subtropical [3,4,10] plants.…”
Section: Introductionmentioning
confidence: 99%
“…CBF, also known as dehydration responsive element (DRE) binding factor (DREB) proteins, are key factors in plant cold response (Liu et al, 1998;Shi et al, 2018). In rice, WRKY genes expressed highly under cold stress and may be involved in ICE-CBF-COR pathway (Guo et al, 2019). In this study, we mainly identi ed 27 chilling response SlWRKY genes based on RNA-seq and qRT-PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%